2016
DOI: 10.1080/14767058.2016.1192118
|View full text |Cite
|
Sign up to set email alerts
|

WISP1 is a novel adipokine linked to metabolic parameters in gestational diabetes mellitus

Abstract: These results demonstrate a relationship between WISP1 and the metabolic parameters of GDM. And, WISP1 might be involved in the pathophysiology of GDM. As a part of this pathophysiological mechanism, the activation of WISP1 and betatrophin might take place through several ways; WISP1 and betatrophin might either use same signaling pathways and potentiate each other or they might also constitute the sequential steps of a common pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 32 publications
5
33
2
Order By: Relevance
“…In contrast, our findings demonstrated that prepregnancy overweight/obesity interacted with GDM to affect circulatory concentration of WISP1 (Figure 1(b)). Similarly, it has been reported that circulating WISP1 in the GDM group is significantly higher than that in the control group [15].…”
Section: Disease Markersmentioning
confidence: 54%
See 1 more Smart Citation
“…In contrast, our findings demonstrated that prepregnancy overweight/obesity interacted with GDM to affect circulatory concentration of WISP1 (Figure 1(b)). Similarly, it has been reported that circulating WISP1 in the GDM group is significantly higher than that in the control group [15].…”
Section: Disease Markersmentioning
confidence: 54%
“…WISP1 is involved in a wide range of biological functions and pathological processes, such as cell growth, differentiation, and survival [13,14]. And overexpressed WISP1 has been observed in several diseases including GDM [15], hypertension [16], obesity [17,18], lung fibroblasts [19], and several types of cancer [20]. WISP1 is widely expressed in normal tissues, particularly in human adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Disorders such as DM affect all systems of the body (10, 11, 5360). For example, DM can negatively impact the immune system, musculoskeletal function, hepatic metabolism, and renal clearance (50, 53, 55, 59, 6164).…”
Section: Increased Lifespan Degenerative Disorders and Cell Injurymentioning
confidence: 99%
“…EPO also fosters microglial survival during oxidative stress through mTOR (206). Given that Wnt signaling and WISP1 are also involved in metabolic pathways (60, 244, 258–261), EPO also provides cellular protection during metabolic disorders through Wnt signaling (262265). …”
Section: Erythropoietin and The Modulation Of Mtormentioning
confidence: 99%
“…WISP1 expression is altered by weight change in humans and increases during insulin resistance in glucosetolerant individuals (Murahovschi et al 2015), suggestive that WISP1 may represent an important reparative process in individuals with DM. However, WISP1 expression has recently been linked to gestational diabetes with additional studies required to determine its role in this disorder (Sahin Ersoy et al 2016).…”
Section: Wisp1 In Cellular Repair and Proliferationmentioning
confidence: 99%